Regulasi Keinsinyuran dalam Konteks ASEAN Mutual Recognition Agreement on Engineering Services - Vicky Septia Rezki; Rina Shahriyani Shahrullah; Elza Syarief (Nagari Law Review, 2022)
Infrastructure development is a benchmark for a country's achievement. Indonesia as developing countries makes various acceleration efforts by increasing the quality and quantity of engineers as the main actor to produce quality development plans. In addition, considering the development of the ASEAN Economic Community (AEC), engineering practice is expected to contribute globally, especially in ASEAN countries. To answer this, the Government of Indonesia issued Act Number 11 of 2014 concerning Engineering and Act Number 2 of 2017 concerning Construction Services. These two Regulation serve as legal protection for the implementation of engineering practice. However, along with the dynamics of political interests, the implementation of these two regulations are actually contradictive and they inherent the ambiguity of the roles of several intersecting institutions related to the engineering profession certification process. Hence this study aims to analyzes the disharmonization of the regulations and to offer solutions. To achieve the aims, the study uses a sociological juridical method that examines the provisions of the two act and examines in depth the realities that exist in society. Beside that, the method use the secondary legal material such as Mutual Recognition Agreement (MRA) on Engineer Service in ASEAN. This article offers a critical approach obtained from the Focus Group Discussion as a public sphere for the gap in engineering practice certification. In this study, it was found that there are gaps in the function and flow mechanism in obtaining competency certificates. This condition has led to a tendency for professional actors to choose an easiest requirement but provide a large access to participate in various government projects. The study concludes that basically the presence of these two acts are beneficial in regulating engineering practices, but they are not supported by massive information and consistency of the government as a regulator and the synergity of the institutions involved in implementing these regulations has not been optimal.